Analisis Pengendalian Persediaan Bahan Baku Berdasarkan Metode Economic Order Quantity Pada Toko Classic Donat Kendari - Wal'afny, Nurma; Mas’ud, Arifuddin; Rahmah, Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2025)
The company's main objective is to achieve profitability through an optimal production process, which is highly dependent on the availability and efficient management of raw materials. Although vital, raw material supplies must be managed optimally—not excessively—for cost efficiency, which requires careful calculation of the ideal purchase quantity and timing. Toko Classic Donat Kendari still implements an inefficient purchasing policy, which is based on estimates (purchasing small quantities when supplies are running low) to prevent spoilage. This study aims to evaluate the control of raw material inventory at Toko Classic Donat Kendari using the Economic Order Quantity (EOQ) method. This study uses a combined qualitative and quantitative approach, with data collection through interviews and documentation. The results of the study indicate that Toko Classic Donat Kendari can control raw material inventory more effectively through the application of the EOQ method. The implementation of EOQ has been proven to optimize ordering costs and storage costs, which overall contribute to a reduction in total inventory costs.